The role of seminal fluid in cervical squamous carcinoma progression: Impact on cell proliferation, EMT, motility and gene expression - Mkwanazi, Nonkululeko (Division of Medical Biochemistry and Structural Biology, 2023)
Cervical cancer is the leading cause of cancer related deaths and the second most common cancer amongst South African women. The key cause for cervical cancer development is sexual transmission and persistent infection with high-risk Human Papillomavirus (HPV). However, it takes several years from infection to cervical cancer development, suggesting that other factors contribute to the disease. Exposure of neoplastic epithelial cells to Seminal Fluid (SF) has been shown to promote cell proliferation in culture and growth of explants in mice injected with HeLa cervical adenocarcinoma cells. Since the majority of cervical cancer cases are squamous cell carcinoma, in this study, we examined the effect of SF on cancer cell proliferation, EMT, motility and gene expression using two squamous cell carcinoma cell line model systems, SiHa and Me180. This study shows that SF significantly enhanced cell proliferation in both cell lines. Using confocal microscopy and phalloidin staining, it was further shown that SF caused morphological changes and induced stress fibre formation. SF upregulated the expression of EMT transcription factors Snail, Twist and ZEB1. EMT induction was confirmed by the increase of N-cadherin and a decrease in E-cadherin protein expression. Additionally, results showed that the induction of EMT transcription factors Snail, Twist and ZEB1 by SF occurs via EP4 receptor, ERK1/2 and COX signaling pathways. To investigate the effect of SF on migration and invasion, transwell migration assays were used. SF significantly enhanced directional cell migration and invasion of SiHa and Me180 cells. Cell invasion was associated with an increase in MMP-2 and MMP-9. SF also induced proinflammatory and angiogenic gene expression in cervical squamous carcinoma cells. SF mediated induction of inflammatory and angiogenic genes was shown to be associated with AP-1 and NFkB transcription factors. A small molecule inhibitor of nuclear import, INI-43 inhibited the nuclear localization and activity of SF activated NF-kB as well as the expression of SF induced inflammatory and angiogenic genes. Employing ectocervical tissue biopsies, SF caused the upregulation of EMT transcription factors, MMPs, inflammatory and angiogenic genes. Taken together, these results suggest that SF may play a role in promoting EMT and enhances the migratory and invasive potential of cervical squamous cell carcinoma. These findings together implicate SF as a possible factor that may promote cervical cancer progression.